Moments of truth: Managing the face-to-face encounter in distance learning - Mary Cull; Robyn Walker (Flexible Learning Association of New Zealand, 2012)
As service providers, distance educators interact with students in a range of ways. Mostly the educators are shielded from the immediacy of any face-to-face encounter with their students. Yet one aspect of many academic courses taught at a distance is the campus or regional course. Managing this crucial service encounter with distance students forms the focus of this paper. Among other strategies, the authors suggest team teaching as a way of enhancing the learning experience for students and optimising the skills and talents of educators.